2017
DOI: 10.1038/s41598-017-14534-2
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone profiling in obese and nonobese women with polycystic ovary syndrome

Abstract: The study explored differences in the steroidogenic pathway between obese and nonobese women with polycystic ovary syndrome (PCOS) using liquid chromatography-tandem mass spectrometry (LC-MS/MS). 1044 women with PCOS (including 350 lean, 312 overweight and 382 obese) and 366 control women without PCOS (including 203 lean, 32 overweight and 131 obese) were enrolled. The differences in steroid hormones were amplified in lean PCOS versus lean controls compared with obese PCOS versus obese controls. Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
2
38
2
1
Order By: Relevance
“…Our previous study revealed that patients with PCOS had higher plasma glucose levels than their corresponding control groups. 16 In addition, the levels of several serum steroid hormones, such as DHEAS, 17-hydroprogesterone and oestrone, were different in lean and obese patients, indicating that androgen, androgen metabolites and other steroid hormones may play a role in the occurrence of obesity and abnormal glucose metabolism.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Our previous study revealed that patients with PCOS had higher plasma glucose levels than their corresponding control groups. 16 In addition, the levels of several serum steroid hormones, such as DHEAS, 17-hydroprogesterone and oestrone, were different in lean and obese patients, indicating that androgen, androgen metabolites and other steroid hormones may play a role in the occurrence of obesity and abnormal glucose metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found that hyperandrogenism can induce insulin resistance in subcutaneous tissue by inhibiting the phosphorylation of protein kinase C, upregulating the uncoupling of protein‐1 expression in brown adipose tissue, or promoting lipolysis in visceral fat cells, thus influencing glucose metabolism. Our previous study revealed that patients with PCOS had higher plasma glucose levels than their corresponding control groups . In addition, the levels of several serum steroid hormones, such as DHEAS, 17‐hydroprogesterone and oestrone, were different in lean and obese patients, indicating that androgen, androgen metabolites and other steroid hormones may play a role in the occurrence of obesity and abnormal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations